An Optimality-Theoretic Study of Contextual Elision in Spoken Iraqi Arabic - Jaleel, Sahar Mohammed; Al-Rashid, Balqis I. G. (Journal of Posthumanism, 2025)
This study investigates the phonological process of contextual elision in Spoken Iraqi Arabic (SIA) in terms of Optimality Theory (OT) by Prince & Smolensky (1993).The variety examined in this study is used in the southern part of Iraq since it is the native dialect of the researcher.The analysis of the data concludes that all the types of contextual elision in SIA, including elision of vowel, consonants and whole syllables can be accounted for within the framework of OT. It is also revealed that certain OT constraints,such as NUCi/u, MAX-IO, -LATERAL and *GEM, compete to generate the elided forms.